Research on an equilibrium development model between urban and rural areas of Henan including carbon sink assets under the dual carbon goal - Xinfa, Tang; Guozu, Hao; Yonghua, Wang; Dan, Li; Yan, Luo (Frontiers in Environmental Science, 2023)
WWith the improvement of China's industrialization and urbanization level, the problem of urban-rural dual structure is becoming more and more obvious. The balanced development of urban and rural areas is a problem that China strives to solve. Under the background of the goal of dual-carbon, urban enterprises reduce carbon emissions, while rural carbon sink potential is huge, carbon optimization becomes the basis of balanced urban-rural development co-occurrence. This paper discusses the construction of urban-rural mutual aid model from the perspective of carbon sink value. Using case study method and system theory research method, this paper analyzes the development status of rural agriculture and farmers, reveals the potential economic value of rural carbon sink assets, constructs the urban-rural mutual aid mechanism of industry back to agriculture, and puts forward the implementation path of urban-rural mutual aid and coordinated development of carbon sink assets under the dual carbon target. The results show that the urban-rural mutual assistance model of carbon sink assets is conducive to the balanced development of urban and rural areas in Henan Province and the common prosperity of the people.